2017
DOI: 10.4049/jimmunol.1700179
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma musculi Infection in Mice Critically Relies on Mannose Receptor–Mediated Arginase Induction by a TbKHC1 Kinesin H Chain Homolog

Abstract: Arginase activity induction in macrophages is an escape mechanism developed by parasites to cope with the host's immune defense and benefit from increased host-derived growth factor production. We report that arginase expression and activity were induced in macrophages during mouse infection by , a natural parasite of this host. This induction was reproduced in vitro by excreted/secreted factors of the parasite. A mAb directed toKHC1, an orphan kinesin H chain from , inhibited excreted/secreted factor-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…On the contrary, previous studies using Yersinia pseudotuberculosis showed that partial inhibition of CD209 between the interaction of hDCS and Y. pseudotuberculosis was achieved only when the triple combination of inhibitors (antireceptor antibodies, mannan oligosaccharide, and purified LPS core) was employed. In this study, even the use of a single inhibitor provided partial protection against Toxoplasma infection as was also observed in Trypanosoma musculi infection (69).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…On the contrary, previous studies using Yersinia pseudotuberculosis showed that partial inhibition of CD209 between the interaction of hDCS and Y. pseudotuberculosis was achieved only when the triple combination of inhibitors (antireceptor antibodies, mannan oligosaccharide, and purified LPS core) was employed. In this study, even the use of a single inhibitor provided partial protection against Toxoplasma infection as was also observed in Trypanosoma musculi infection (69).…”
Section: Discussionsupporting
confidence: 75%
“…Similar results were reported in a study involving T. musculi and T. cruzi whose results showed enhanced survival in macrophages, whereas receptor blockade decreased parasite growth (69). A number of studies using different antibodies and different strains of knock-out mice have yielded a wide array of contradicting results (11,(70)(71)(72)(73)(74).…”
Section: Discussionsupporting
confidence: 72%
“…Treatment with mannose also reduced parasitemia in mice infected by T. musculi . However, whereas TbKHC1 facilitates Tbb parasitemia via the SIGN-R1 receptor, the MMR receptor was apparently the main target of T. musculi ES ( 138 ). This suggests that kinesin heavy chain-related proteins play similar roles in promoting infection in two genetically distant trypanosomes, via macrophage arginase induction, following distinct CLR targeting.…”
Section: Macrophage L -Arginine Metabolism Dysregumentioning
confidence: 99%
“…The secretome, (excreted/secreted factors), of trypanosomes is a complex mixture of proteins, carbohydrates and lipids excreted from the surface of the parasite or secreted via exocytotic vesicles by a parasite‐specific organelle called the flagellar pocket . Some of these components are implicated in T brucei evasion of host innate response and others in the virulence process .…”
Section: Introductionmentioning
confidence: 99%
“…The secretome, (excreted/secreted factors), of trypanosomes is a complex mixture of proteins, carbohydrates and lipids excreted from the surface of the parasite or secreted via exocytotic vesicles by a parasite-specific organelle called the flagellar pocket. [12][13][14] Some of these components are implicated in T brucei evasion of host innate response 15,16 and others in the virulence process. [17][18][19][20][21] Because of the fundamental role of DCs during trypanosomiasis but limited human data, we investigated the effects of T gambiense and its secretome on human monocytes-derived DCs.…”
mentioning
confidence: 99%